Restoration of the Elementary School "Johann Heinrich Pestalozzi"-Skopje - Papasterevski, Dimitar; Radevski, Aleksandar (Scientific Foundation SPIROSKI, 2021)
The post-earthquake rebuilding of Skopje provided valuable examples of modernist architecture that deserve to be included in the category of a protected building heritage. A prominent instance is the elementary school named after the famous Swiss educator and pedagogue "Johann Heinrich Pestalozzi", the first example in this area that introduces the practical application of deeply thought-out methods of integral education promoted by him in the early 19th century. Many contemporary architects have incorporated the efficient use of this educational concept, including the renowned Swiss architect Alfred Roth, creating a unique sample of a school that includes specific geographic and regional features (climatic, seismic, cultural - aesthetic). In terms of properties, the building contains originality, rarity, and aesthetic-artistic value. With reference to other criteria, it also includes the value of authentic preservation, which is in crisis without adoption of adequate and prompt protection and restoration measures. In respect of protecting the school from further destruction, the Swiss Embassy in Skopje made an official request for a study and design documents for the school reconstruction by detecting all critical issues, developed and executed by the expert team from the Faculty of Architecture in Skopje. This paper, which is based on the results of the research, conducted by us as a part of the group, aims to elaborate the methodological approach of the analyses contained in the study, which, as a pre-design procedure, provided a solid base for developing design documents. A significant component of the study that needs to be emphasized was the use of computer technology throughout the work process, using parametric insertion of structural and other elements of the building's architecture into a 3D model. This approach allowed the generation of architectural details across any part of the facility in an exact form, which proved extremely useful through the process of constructing the design documents.